2020
DOI: 10.3390/d12010028
|View full text |Cite
|
Sign up to set email alerts
|

Thalassic Rotifers from the United States: Descriptions of Two New Species and Notes on the Effect of Salinity and Ecosystem on Biodiversity

Abstract: This study shows the results of a rotifer faunistic survey in thalassic waters from 26 sites located in northeastern U.S. states and one in California. A total of 44 taxa belonging to 21 genera and 14 families were identified, in addition to a group of unidentifiable bdelloids. Of the fully identified species, 17 are the first thalassic records for the U.S., including Encentrum melonei sp. nov. and Synchaeta grossa sp. nov., which are new to science, and Colurella unicauda Eriksen, 1968, which is new to the Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…All rotifers (Bdelloidea, Monogononta, and Seisonacea, with the exclusion of Acanthocephala) belong to meiofauna as they are minute in size, usually between 0.05 and 1 mm ; some species can be found in the meiobenthos, others in the zooplankton, and also as epibionts or in the periphyton (Wallace et al 2006). They are mostly freshwater and limno-terrestrial organisms, but several species can be found in haline habitats: out of more than 2000 known rotifer species, about 450 have been found in marine waters (Fontaneto et al 2006;Leasi & De Smet 2020). Of these, 90 are known to occur along the Italian coasts, including seven bdelloids, 81 monogononts, and two seisonaceans (De Smet et al 2015).…”
Section: Rotiferamentioning
confidence: 99%
“…All rotifers (Bdelloidea, Monogononta, and Seisonacea, with the exclusion of Acanthocephala) belong to meiofauna as they are minute in size, usually between 0.05 and 1 mm ; some species can be found in the meiobenthos, others in the zooplankton, and also as epibionts or in the periphyton (Wallace et al 2006). They are mostly freshwater and limno-terrestrial organisms, but several species can be found in haline habitats: out of more than 2000 known rotifer species, about 450 have been found in marine waters (Fontaneto et al 2006;Leasi & De Smet 2020). Of these, 90 are known to occur along the Italian coasts, including seven bdelloids, 81 monogononts, and two seisonaceans (De Smet et al 2015).…”
Section: Rotiferamentioning
confidence: 99%